Synucleins and Gene Expression: Ramblers in a Crowd or Cops Regulating Traffic? - Surguchev, Alexei A.; Surguchov, Andrei (Frontiers in Molecular Neuroscience, 2017)
Synuclein family consists of three members, alpha, beta and gamma-synuclein which are thoroughly investigated for almost 30 years, because of their involvement in human diseases. Since the first synuclein discovery in the brain of the electric ray Torpedo californica, members of this family have been identified in all vertebrates, and comparative studies have indicated that synucleins are evolutionary conserved. They are small naturally unfolded proteins prone to aggregate, easily change their conformation and bind to membranes. The genes for alpha, beta and gamma-synuclein have different chromosomal localization and have a well preserved general organization composed of five coding exons of similar size. Three genes encoding synucleins are present in the majority of vertebrates, however, a variable number of synuclein genes are described in fishes of different species. The biggest question in the field is regarding their normal physiological function in cells and tissues. alpha-Synuclein is implicated in the regulation of synaptic activity through regulation of synaptic vesicle release, while the physiological functions of two other members of the family is less clear. Here we discuss recent results describing their role in the regulation of protein expression.